The re-discovery in Sumatra of a rarely seen moth, Heterosphecia tawonoides, and its identification using citizen science platform iNaturalist. - Andrea Molyneaux (Universitas Pakuan, 2023)
Traditional methods of species identification involve collection and killing of specimens. The associated costs and expertise required are prohibitory. In this paper we describe the first documented record of Heterosphecia tawonoides in its natural habitat in Sumatra since 1887, reporting its identification using photographs uploaded to citizen science platform iNaturalist. Our findings add valuable information to the small body of work on this species and demonstrate the importance of having freely available high quality tools such as iNaturalist without which this important record would not have been reported and the observation of this rarely seen moth species in Sumatra would have remained unknown.